Pengaruh sport massage terhadap kenyamanan atlet seni tunggal baku pencak silat MTsN 2 lombok timur tahun 2024 - Yolanda Ayusetiawati; Lalu Suprawesta; Muhsan (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
Massage has long been known to humans, especially people from the east, this massage has been done for centuries by our ancestors. Massage is a simple manipulation that is often used by people around us to overcome discomfort in parts of the body. Massage is an art of hand movement which has the aim of gaining fitness, recovering from injuries, curing disease, and supporting sports and work performance. The mechanical effect of hand movements during this massage will create a feeling of calm, comfortable relaxation, and create a refreshing feeling in the recipient's body. The aims of this research are (1) To determine the effect of sports massage on increasing feelings of comfort for athletes in the single art of standard pencak silat MTsN 2 East Lombok in 2024. This research is experimental research with a quantitative descriptive approach. The research population was 20 MTsN 2 East Lombok MTsN 2 East Lombok martial arts athletes. The sample for this study was 10 people who were determined using purposive sampling techniques. Data was collected using a questionnaire. Data analysis was carried out using quantitative descriptive analysis. The results of the research show that there is a difference in the influence of sports massage before and after training on the comfort of athletes in the single art of pencak silat standard MTsN 2 East Lombok in 2024 where sports massage after training has more influence on the athlete's level of comfort with a calculated t value of 13.639 while the t table is 2.262, this means that t count > t table, namely 13.639 > 2.262 and the p value = 0.05.